Lumbar puncture under fluoroscopy guidance: a technical review for radiologists - Özütemiz, Can (Diagn Interv Radiol, 2019)
There are many differences in fluoroscopy-guided lumbar puncture (FG-LP) technique among radiologists. Even within the same institution, there are a variety of preferences among proceduralists with individual perspectives based on the literature, training, and/or experience. Our aim is to provide familiarity with various techniques involved in FG-LP and provide insight on how to improve patient outcomes. The pertinent anatomy and physiology, indications, contraindications, patient management, complications of the procedure, and procedural techniques for performing an FG-LP are reviewed in detail. Potentially controversial topics regarding FG-LP are also addressed.